2020
DOI: 10.1016/j.jvir.2020.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation for the Palliative Treatment of Bone Metastases: Outcomes from the Multicenter OsteoCool Tumor Ablation Post-Market Study (OPuS One Study) in 100 Patients

Abstract: Purpose: To evaluate the effectiveness of radiofrequency (RF) ablation as measured by change in worst pain score from baseline to 3 mo after RF ablation for the palliative treatment of painful bone metastases.Materials and Methods: One hundred patients (mean age, 64.6 y) underwent RF ablation for metastatic bone disease and were followed up to 6 mo. Subjects' pain and quality of life were measured before RF ablation and postoperatively by using the Brief Pain Index and European Quality of Life questionnaires. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 26 publications
1
59
0
1
Order By: Relevance
“…There was significant improvement in pain (8.2 ± 1.7 at baseline to 3.5 ± 3.2 at 6 months), pain interference and QOL. 162 The increasing number of prospective studies utilizing RFA with or without cement augmentation continue to demonstrate the safety and efficacy of this treatment with a more rapid rate of pain relief (0–2 weeks) compared to conventional fractionated radiotherapy (4–6) weeks. 163 Current therapies and treatments involve a combination of analgesics, bisphosphonates, and radiotherapy with variable results and many patients experiencing inadequate pain relief.…”
Section: Data Evaluation and Discussionmentioning
confidence: 99%
“…There was significant improvement in pain (8.2 ± 1.7 at baseline to 3.5 ± 3.2 at 6 months), pain interference and QOL. 162 The increasing number of prospective studies utilizing RFA with or without cement augmentation continue to demonstrate the safety and efficacy of this treatment with a more rapid rate of pain relief (0–2 weeks) compared to conventional fractionated radiotherapy (4–6) weeks. 163 Current therapies and treatments involve a combination of analgesics, bisphosphonates, and radiotherapy with variable results and many patients experiencing inadequate pain relief.…”
Section: Data Evaluation and Discussionmentioning
confidence: 99%
“…These findings are possible because careful attention was made to follow a well-codified anesthetic/pain management protocol which was strictly applied for each patient. Previous studies on RFA in the bone metastases report either the use of general anesthesia or conscious sedation [ 18 , 28 ]. However, a previous study assessing radiofrequency of extra axial metastasis has shown the feasibility of RF procedure under local anesthesia alone [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study concluded that POP has a weak antitumor effect and that PMMA infusion increases the risk of cancer cells entering the circulation within minutes after injection. So, ablation can be performed before cement infusion to obtain better local tumor control [27] , [30] , [31] . Levy [31] conducted a multicenter study that included 100 cases, 97 of which were treated with cementoplasty combined with radiofrequency ablation therapy.…”
Section: Commonly Used Minimally Invasive Treatment Methodsmentioning
confidence: 99%